Manajemen Pembelajaran Aswaja NU Di Madrasah Aliyah Unggulan (MAU) Hikmatul Amanah Pacet Mojokerto Tahun Ajaran 2019/2020 - Syamsul Bahri (Urwatul Wutsqo: Jurnal Studi Kependidikan dan Keislaman, 2021)
The results of the study were known that the management of learning Aswaja Annahdhliyah at the favorite Madrasah Aliyah Hikmatul Amanah Pacet Mojokerto in 2019/2020 conducted through 1) Lesson plan of Aswaja An-Nahdliyah outside the class was by reading the Prophet's blessings, Istighatsah, Wiridan, Yasinan, Tahlil and dalil annajah, while the lesson plan of Aswaja An-Nahdliyah in the classroom was by preparing learning tools, materials, learning resources, methods and customized media. 2) The implementation of learning Aswaja an-Nahdliyah outside of class was by habituation of the practices of Aswaja Annahdliyah, self-development, while the implementation of learning Aswaja An-Nahdliyah in the classroom was through opening, main and closing activities as well as using learning resource books, methods and media learning. 3) Evaluation of Aswaja An-Nahdhliyah learning was conducted with formative, summative, and diagnostic by daily task either written or spoken, the middle of semester, the end of semester, practice and the assessment of student weakness and factors of the cause.